Integrating Social Work Services in an Established Low Vision Service: Lessons Learned from a One-Year Pilot Program. - Squier, Karen (Optometry & Visual Performance, 2026)
Background: Individuals with visual impairment face challenges in addressing transportation access, employment placement, and mental health awareness and counseling. Accessing resources is difficult for patients and providers lacking training. Social workers can bridge these gaps. This paper reviews lessons from integrating a new social work service into an existing low vision clinic. Methods: The Low Vision Service at The Eye Center of the Southern College of Optometry received a private grant to hire a social worker (SW) for one year. The social worker kept a log of all the patients with whom she interacted during this term. Using the patient logs, a record review and assessment of interactions with each patient were evaluated. Results: The SW evaluated 236 patients. Case management and referrals comprised the majority of the SW’s efforts, as requested by patients. Counseling and emotional support were rarely implemented by the SW. Program sustainability was a challenge. Conclusions: While our program provided requested support to our patients, it functioned more as a patient navigation and case management program than one that highlighted the SW’s expertise. Incorporating patient input and creating a structured internal program and education for appropriate referrals, as directed by the SW, would have provided an opportunity for a more robust program highlighting the key skills a SW can offer.